Mario Slugan: Montage as Perceptual Experience. Berlin Alexanderplatz from Döblin to Fassbinder. - Jovanovic, Nenad (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2018)
Nenad Jovanovic's review of the book Montage as Perceptual Experience. Berlin Alexanderplatz from Döblin to Fassbinder by Mario Slugan